Improved tribological performance of epoxy composites containing core–shell PE wax@SiO2 nanoparticles. Issue 9 (4th July 2022) - Zhao, Gengrui; Li, Jiajun; Wang, Honggang; Chen, Shengsheng; Li, Zhenyu; Lv, Bo; Liu, Wenguang; Gao, Gui; Ren, Junfang; Yang, Dongya
Abstract: The poor tribological performance of epoxy limits its application in the field of lubrication and wear protection, but there is still great potential for improvement. In this paper, polyethylene wax contained by silica core–shell particles was prepared and incorporated into the epoxy resin. The effects of particle content, normal load, and reciprocating linear velocity on the friction and wear properties of epoxy‐based composites were investigated. Due to the lubricating and anti‐wear effect of core–shell particles, the 10 wt.% amount can reduce at most the friction coefficient and wear rate of epoxy by 57% and 94%, respectively. The inflatable and burst core–shell particles, transfer film, and corrosion were observed on the worn surface. A mechanism referring to fracture, the release of lubricating core, and transfer film formed by a mixture of core and shell materials were deduced to explain the enhancement effect of core–shell particles in the epoxy matrix. That also suggests that the polyethylene wax@silica core–shell particles will be a potential lubricating and wear‐resistant additive of epoxy. Abstract : The fracture of core‐shell particles, the release of PE wax core and the formation of transfer film consisting of a mixture of SiO2 shell and PE wax core occur at the friction surface, which attributes to the enhanced tribological performances of PE wax @ SiO2 /epoxy composites.